The Effect of Attitude, Subjective Norms, Perceived Behavioral Control and Environmental Concern on Electric Vehicle Adoption Intention - Fajar Satria Darma; Sri Padmantyo (Majapahit Journal of Islamic Finance and Management, 2025)
The primary objective of this research is to examine how individuals’ intentions to adopt electric vehicles are shaped by their personal attitudes, the perceived expectations of others (subjective norms), their sense of control over the behavior (perceived behavioral control), and their level of environmental consciousness. Adopting a quantitative methodology, the research focuses on Indonesian citizens who express a willingness to shift toward electric vehicle usage. A purposive sampling technique was applied to recruit 220 respondents, with data collected through a structured Likert-scale questionnaire. The analysis employed PLS method using SMARTPLS version 4.0, covering both measurement and structural model assessments. The results indicate that positive attitudes, perceived behavioral control, and environmental concern significantly enhance the intention to adopt electric vehicles. In contrast, subjective norms did not show a statistically meaningful effect. On a theoretical level, this research extends TPB by applying it to the context of electric vehicle adoption in Indonesia. From a practical standpoint, the findings offer important guidance to policymakers and relevant stakeholders in formulating effective strategies to encourage widespread adoption of electric vehicles throughout the country.